Adaptive Backstepping Integral Sliding Mode Control Combined with Super-Twisting Algorithm For Nonlinear UAV Quadrotor System - Nettari, Yakoub; Labbadi, Moussa; Kurt, Serkan (ELSEVIER, 2022)
Quadrotors are extremely agile UAVs with many uncertainties related to their moment of inertia, drag coefficients, and mass. Besides aerodynamic turbulence, the quadrotor is rich in non-linearity due to its underactuated mechanical system. These last two factors lead to problems that require adaptive and robust control. This research paper describes a new hybrid robust nonlinear control technique for a quadrotor. First, a combination of backstepping and sliding-mode approaches based on proportional integral derivative modified surfaces is developed to address the quadrotor trajectory tracking problem, where the Lyapunov method is used to evaluate the control system's stability. Second, adaptive technique combined with sliding mode control to estimate the various parameters of the proposed controller. Super-Twisting algorithm is examined in order to minimize the chattering impact of sliding mode control. To reduce the error convergence time and to increase the performance of speed tracking, a novel super-twisting adaptive backstepping PID sliding mode approach is presented for the quadrotor rotational and translational subsystems. Simulation results are shown to demonstrate the efficacy and practicality of the proposed control. To illustrate the superiority and the designed control technique's effectiveness, a comparative analysis is performed with different newly developed controllers. Copyright (c) 2022 The Authors. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0/)
Keywords: Backstepping; Sliding mode; Adaptive law; Super-twisting; Euler-Newton; Quadrotor System; TRAJECTORY TRACKING; HELICOPTER; Automation & Control Systems